Sustainable phosphorus loadings from effective and cost-effective phosphorus management around the Baltic Sea. - Andreas C Bryhn (Public Library of Science (PLoS), 2009)
Nutrient over-enrichment of the Baltic Sea, accompanied by intensified algal blooms and decreasing water clarity, has aroused widespread concern in the surrounding countries during the last four decades. This work has used a well-tested dynamic mass-balance model to investigate which decrease in total phosphorus loading would be required to meet the environmental goal to restore the trophic state in the Baltic Sea to pre-1960s levels. Furthermore, the extent to which various abatement options may decrease the phosphorus loading in a cost-effective manner has been studied. Upgrading urban sewage treatment in the catchment could, alone or in combination with banning phosphates in detergents, be sufficient to meet the set environmental goal, at an estimated annual basin-wide cost of 0.21-0.43 billion euro. Such a plan would potentially decrease the total phosphorus loading to the Baltic Sea with 6,650-10,200 tons per year.